Intramolecular carbolithiation of N-allyl-ynamides: an efficient entry to 1,4-dihydropyridines and pyridines – application to a formal synthesis of sarizotan - Gati, Wafa; Rammah, Mohamed M.; Rammah, Mohamed B.; Evano, Gwilherm (Beilstein Journal of Organic Chemistry, 2012)
We have developed a general synthesis of polysubstituted 1,4-dihydropyridines and pyridines based on a highly regioselective lithiation/6-endo-dig intramolecular carbolithiation from readily available N-allyl-ynamides. This reaction, which has been successfully applied to the formal synthesis of the anti-dyskinesia agent sarizotan, further extends the use of ynamides in organic synthesis and further demonstrates the synthetic efficiency of carbometallation reactions.
Keywords: carbolithiation; carbometallation; dihydropyridines; organolithium reagents; pyridines; sarizotan; ynamides